Comparative study on metal/CFRP hybrid structures under static and dynamic loading - Zhu, Guohua; Liao, Jiapeng; Sun, Guangyong; Li, Qing (International journal of impact engineering, 2020)
•Experimentally and numerically investigated the crashworthiness of Metal/CFRP hybrid structures under quasi-static and dynamic loading conditions.•Explored the energy absorption mechanics of the hybrid tubes.•Explored the influences of aluminum wall thickness, fiber orientation and interfacial strength on crashworthiness of the hybrid tubes. This study aims to explore the crushing behavior of aluminum (AL) - carbon fiber reinforced plastic (CFRP) tubes with different hybrid configurations subjected to quasi-static and dynamic loading conditions. First, a series of experimental tests are carried out to explore the crushing behaviors of hybrid tubes in comparison with the corresponding individual tubes made of single material. The experimental results indicate that the H-II hybrid tube, made of an outer aluminum circular tube and internally adhered CFRP layers, generates a unique deformation pattern; whose outer aluminum tube inverses externally and inner CFRP layers crush progressively. With these distinctive deformation features, the H-II hybrid tubes are considered to be ideal with superior crashworthiness and energy-absorbing capacity. It is also found that loading rate has little influence on deformation pattern of hybrid tubes and single material tubes, while energy-absorbing capacity of hybrid tubes and individual CFRP tubes under dynamic loading are substantially lower than those under quasi-static loading. Second, numerical simulations are performed for the H-II hybrid tubes to provide further insights into their underlying energy-absorbing mechanisms. It is found that the external inversion mode of the outer aluminum tube is the major energy-absorbing mechanism, in which the contribution of the outer aluminum tube to total energy absorption decreases with increase in thickness of CFRP layers. The internal energy of the externally inversed aluminum tube is considerably higher than internal energy of typical progressively-folded AL tube (sole aluminum tube). Third, a parametric study is further conducted, which indicates that with increasing aluminum wall thickness, the specific energy absorption (SEA) increases. Besides, it is found that varying fiber orientation of inner CFRP layers leads to no evident change in the deformation mode and SEA of the H-II hybrid tubes. When the interfacial strength in between aluminum and CFPR reaches a certain level, there is no evident increase in the total energy absorption with further increase of the interface strength, but the initial peak crushing force increases notably. These results are expected to deepen the understanding of crushing behavior of the H-II hybrid tubes, thereby providing guidance for the crashworthiness design.